Efficient electron-induced removal of oxalate ions and formation of copper nanoparticles from copper(II) oxalate precursor layers - Rückriem, Kai; Grotheer, Sarah; Vieker, Henning; Penner, Paul; Beyer, André; Gölzhäuser, Armin; Swiderek, Petra (Beilstein Journal of Nanotechnology, 2016)
Copper(II) oxalate grown on carboxy-terminated self-assembled monolayers (SAM) using a step-by-step approach was used as precursor for the electron-induced synthesis of surface-supported copper nanoparticles. The precursor material was deposited by dipping the surfaces alternately in ethanolic solutions of copper(II) acetate and oxalic acid with intermediate thorough rinsing steps. The deposition of copper(II) oxalate and the efficient electron-induced removal of the oxalate ions was monitored by reflection absorption infrared spectroscopy (RAIRS). Helium ion microscopy (HIM) reveals the formation of spherical nanoparticles with well-defined size and X-ray photoelectron spectroscopy (XPS) confirms their metallic nature. Continued irradiation after depletion of oxalate does not lead to further particle growth giving evidence that nanoparticle formation is primarily controlled by the available amount of precursor.
Keywords: copper(II) oxalate; electron-induced reactions; layer-by-layer deposition; nanoparticle formation; thin film